Comparison of structures in zircons from lunar and terrestrial impactites - Pidgeon, Robert; Nemchin, Alexander; Kamo, S. (National Research Council Canada, 2011)
There have been a number of reports of the presence of shock features, such as planar fracturing and granulation, the transformation of zircon to reidite, and the breakdown of zircon to baddeleyite in zircons associated with terrestrial impacts. It has also been proposed that the progressive development of these shock features, and the degree of disturbance of the zircon U–Pb isotopic system, could be used as a qualitative measure of the shock pressures and postshock temperatures of the impact. Such behaviour of zircon from terrestrial impacts could be potentially useful in interpreting structures and U–Pb isotopic behaviour of shocked zircons from lunar impactites. However, careful examination of over one hundred zircon grains from samples of lunar breccias from Apollo 14 and 17 have not revealed any grains with terrestrial-like shock features, such as planar deformation features (PDFs), and we have not observed the high-pressure zircon phases reidite or the breakdown of zircon to baddeleyite in zircon grains from the breccias. Most lunar zircon grains show no evidence of a disturbance of their U–Pb systems. However, we have identified a few zircons from lunar breccias that have characteristic internal structures and accompanying Pb loss that we attribute to extreme shock. These structures differ from shock features reported for zircons associated with terrestrial impacts. Whether terrestrial-like impact features were present in the lunar zircons and have been removed during transport and heating in the impact ejecta, or whether these features never developed in the first place, has not been resolved.